A SURVEY OF VIABLE RESOURCES OF AUTONOMOUS WIRELESS MICRO SENSORS IN BIOMEDICAL APPLICATIONS (International Journal of Food and Nutritional Sciences, 2023)
In the fields of computer science and healthcare application sectors, wireless sensor network (WSN) technologies are regarded as one of the most important study areas for the purpose of bettering people's overall quality of life. Sensor networks make it possible for data collection and computing should be thoroughly included into the setting in which they being gathered. Machine intelligence (AI), fitness trackers, home automation, and research and development (IT) had come together to build a new interdisciplinary field of biomedicine. The goal of this branch is to develop solutions to the problems that are encountered in everyday life. Integration of sensing technologies and consumer electronics technologies is one potential use in this field. Such an application would make it possible to continuously monitor individuals. The primary purpose of this research is to carry out an investigation into the available resources of self-sufficient wireless micro sensors that can be used in medical applications. The methodology that was utilised in this research was a systematic literature review. The ability to track, monitor, research, comprehend, and respond to a specific occurrence or event is this wireless sensor technology's key advantage. It is possible to draw the conclusion from this research that the development of mobile iot devices still has a long way to go. The first-line anticipated development for use in coming Heterogeneous networks and the possibilities with their consumer product are currently centred on science is a discipline therapeutic diagnostics are quite encouraging.